STRATEGI KOMUNIKASI PELAYANAN BURGER KING BLOK M PLAZA (JAKARTA) DALAM MENINGKATKAN KEPUASAN KONSUMEN - Syahwa Nurfahrani; Robbikal Muntaha Meliala; Teguh Tri Susanto (Departemen Ilmu Komunikasi Universitas Andalas, 2026)
This study aims to examine the service communication strategy of Burger King Blok M Plaza (Jakarta) in order to improve customer satisfaction. The background of the study comes from the tight competition in the fast-food restaurant industry and the importance of communication quality in developing customer loyalty. This research applies a descriptive qualitative approach, with data collected through observation, interviews, documentation, and literature review. The informants in this study include managers, team leaders, crew members, and customers of Burger King Blok M Plaza. The findings show that internal communication strategies were carried out through vertical and horizontal communication, regular briefings, and employee training to ensure service readiness. In contrast, external communication strategies were implemented through friendly service, the use of social media, digital applications, and special programs such as King Jr. Member for children and birthday surprise events that deliver a personalized experience for customers. The application of the five SERVQUAL dimensions tangibility, reliability, responsiveness, assurance, and empathy reflects a reasonably good quality of service. Customers are satisfied with the services provided, though some suggested improvements to restaurant facilities and dining area comfort. The study concludes that the service communication strategy practiced by Burger King Blok M Plaza plays an important role in increasing customer satisfaction.